Serological indication of chronic inflammatory demyelinating polyneuropathy as an extrahepatic manifestation of hepatitis E virus infection - Pischke, S.; Kjasimov, A.; Skripuletz, T.; Casar, C.; Bannasch, J.; Mader, M.; Huber, S.; Konen, F.; Wolski, A.; Horvatits, T.; Gingele, S.; Peine, S.; et al. (Scientific reports, 2024)
Guillain–Barré syndrome and neuralgic amyotrophy have been associated with hepatitis E virus (HEV) genotype 3 infections, while myasthenia gravis (MG) has been associated with HEV genotype 4 infections. However, whether chronic inflammatory demyelinating polyneuropathy (CIDP) is associated with HEV infections has not been conclusively clarified yet. 102 CIDP patients, 102 age- and sex-matched blood donors, 61 peripheral neuropathy patients (non-CIDP patients), and 26 MG patients were tested for HEV and anti-HEV IgM and IgG. Sixty-five of the 102 (64%) CIDP patients tested positive for anti-HEV IgG and one (1%) for anti-HEV IgM. No other patient tested positive for ati-HEV IgM. In the subgroup of CIDP patients with initial diagnosis (without previous IVIG treatment), 30/54 (56%) tested positive for anti-HEV IgG. Anti-HEV rates were significantly lower in blood donors (28%), non-CIDP peripheral neuropathy patients (20%), and MG patients (12%). No subject tested positive for HEV viremia. CSF tested negative for in 61 CIDP patients (54 patients with primary diagnosis). The development of CIDP but not non-CIDP polyneuropathy may be triggered by HEV exposure in an HEV genotype 3 endemic region. The increased anti-HEV seroprevalence in CIDP patients is not a consequence of IVIG therapy.